Genetic and environmental effects on physical fitness and motor performance - Okuda, E.; Horii, D.; Kano, T. (International Journal of Sport & Health Science, 2005)
The purpose of this study was to estimate genetic and environmental effects on physical fitness and motor performance. Subjects for this study were 90 pairs of monozygotic twins (MZ) and 68 pairs of dizygotic twins (DZ), a total of 316 subjects between 10 to 15 years old. Six items were used for physical fitness and motor performance data: grip strength, sit-ups, sit and reach, side step, 50 meter run and standing broad jump. The correlation analysis and the model-fitting analysis have been done based on the type of each set of twins. For the model-fitting analysis, models that give effects of additive genes (A), nonadditive genes (D), common environment (C), and specific environment (E) on phenotypes of physical fitness and motor performance have been applied. The following could be presumed as a result of a correlation analysis: the results showed for the grip strength and the side step that rMZ was greater than rDZ, and rDZ was greater than half of rMZ, therefore, it could be stated that there were effects from additive genetic and common environmental factors. The results from the sit-ups and the 50 meter run showed that rMZ and rDZ were almost equal to each other, therefore, it could be stated that there was no genetic effect. The correlation ratio of rMZ and rDZ was 2:1 for the category of sit and reach, therefore, the resemblance among MZ was from the genetic effect only. As for the standing broad jump, rDZ was smaller than half of rMZ, therefore, there were effects of additive genetic and nonadditive genetic factors. From the results of the model-fitting analysis, the following could be stated: the best fitting models for grip strength, sit and reach, and the standing broad jump, where additive genetic and specific environmental factors affect phenotypes, were the AE model, and the coefficient of determination of additive genetic factor, at between 52.2% and 76.9%, was relatively high. For the side step, where additive genetic, common environmental and specific environmental factors have effects on phenotypes, the best fitting model was the ACE model, and each coefficient of determination was 32.4%, 39.4% and 28.1%. No genetic effect was observed for sit-ups and the 50 meter run. The coefficient of determination for sit-ups was 51.1% in a common environment and was 48.9% in a specific environment. S-CE was the best fitting model for the 50 meter run, where the effect varies depending on sex, and the coeffi cient of determination for boys were 75.5% for common environment and 24.4% for specific environment, whereas those for girls were 53.0% and 46.9% respectively.